Adult-type rhabdomyoma of the thyroid: A case report - Jiang, ZhenPeng; Zhang, MengNi; Huang, JiaYan; Song, Ling; Lu, Qiang (Frontiers in Oncology, 2023)
Adult-type rhabdomyoma (AR) is a benign myogenous neoplasm. It is rarely located in the thyroid. We present a case of a 61-year-old man, presenting with complaints of a mass found in his left neck for three years. Ultrasonography and computed tomography showed a mass in the left lobe of the thyroid. Subsequently, a fine-needle aspiration biopsy showed that the lesion was suspected to be an oncocytic neoplasm, and the patient underwent surgery. Finally, the lesion was confirmed to be an AR of the thyroid by postoperative pathological diagnosis. In conclusion, AR that occurs in the thyroid is remarkably rare. No case reports to date have described in detail the imaging findings of AR in the thyroid. This study demonstrates the imaging characteristics of a patient with AR of the thyroid, in order to provide more extensive insights to consider the differential diagnosis of thyroid lesions.